Solid electrolyte material and battery using same
By using solid electrolyte materials composed of Li, Ca, Y, Gd and X, and using mechanochemical run-in method to prepare, the problem of insufficient lithium ion conductivity in the prior art is solved, high lithium ion conductivity and good battery performance are achieved, and the safety of the material is improved.
Patent Information
- Application Number
- JP2021550622
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-09-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-09-18
AI Technical Summary
In the prior art, the lithium ion conductivity of the solid electrolyte material is insufficient, making it difficult to meet the high requirements for conductivity of high-performance batteries.
The solid electrolyte material composed of Li, Ca, Y, Gd and X (where X is F, Cl, Br or I) is prepared by mechanochemical run-in method to improve the lithium ion conductivity of the material.
High lithium ion conductivity is achieved, the charging and discharging performance of the battery is improved, and the material is safer due to its non-sulphur content, which avoids the formation of hydrosulfide.
Smart Images

Figure 0007664530000003 
Figure 0007664530000004 
Figure 0007664530000005
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte material and a battery using the same.
Background Art
[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte.
[0003] Patent Document 2 discloses a solid electrolyte material represented by the composition formula Li 6-3z Y z X6 (0 < z < 2, X = Cl or Br).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0005] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity.
Means for Solving the Problems
[0006] The solid electrolyte material of the present disclosure contains Li, Ca, Y, Gd, and X, and X is at least one element selected from the group consisting of F, Cl, Br, and I.
Effects of the Invention
[0007] The present disclosure provides a solid electrolyte material having high lithium ion conductivity.
Brief Description of the Drawings
[0008] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment. [Diagram 2] FIG. 2 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of a solid electrolyte material. [Diagram 3] FIG. 3 is a graph showing a Cole-Cole diagram of the impedance measurement results of the solid electrolyte material according to Example 1. [Figure 4] FIG. 4 is a graph showing the initial discharge characteristics of the battery according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0010] (First embodiment) The solid electrolyte material according to the first embodiment contains Li, Ca, Y, Gd, and X. X is at least one element selected from the group consisting of F, Cl, Br, and I.
[0011] The solid electrolyte material according to the first embodiment has high lithium ion conductivity. Therefore, the solid electrolyte material according to the first embodiment can be used to obtain a battery with excellent charge / discharge characteristics. An example of such a battery is an all-solid-state secondary battery.
[0012] The solid electrolyte material according to the first embodiment desirably does not contain sulfur. A solid electrolyte material that does not contain sulfur is excellent in safety because hydrogen sulfide is not generated even when exposed to the atmosphere. Such a solid electrolyte material can be used to obtain a battery with excellent safety. Note that hydrogen sulfide may be generated when the sulfide solid electrolyte disclosed in Patent Document 1 is exposed to the atmosphere.
[0013] In order to enhance the ionic conductivity of the solid electrolyte material, the solid electrolyte material according to the first embodiment may be substantially composed of Li, Ca, Y, Gd, and X. Here, "the solid electrolyte material according to the first embodiment is substantially composed of Li, Ca, Y, Gd, and X" means that the molar ratio of the total amount of substance of Li, Ca, Y, Gd, and X to the total amount of substance of all elements constituting the solid electrolyte material according to the first embodiment is 90% or more. As an example, the molar ratio may be 95% or more.
[0014] The solid electrolyte material according to the first embodiment may contain elements that are inevitably mixed in. Examples of such elements are hydrogen, nitrogen, or oxygen. Such elements may be present in the raw material powder of the solid electrolyte material or in the atmosphere for producing or storing the solid electrolyte material.
[0015] X may be at least one element selected from the group consisting of Cl and Br. Such a solid electrolyte material has high lithium ion conductivity.
[0016] The solid electrolyte material according to the first embodiment may be a material represented by the following composition formula (1). Li 6-2a-3d Ca a (Y 1-b Gd b ) d Br 6-c Cl c (1) Here, the following formula 0 <a<3、 0 <b<1、 0 <c<6、および 0 <d<1.5、 The material represented by the composition formula (1) has high lithium ion conductivity.
[0017] In order to increase the ionic conductivity of the solid electrolyte material, in the composition formula (1), the formula: 0.01≦a≦0.3 may be satisfied, or the formula: 0.05≦a≦0.3 may be satisfied. In order to further increase the ionic conductivity of the solid electrolyte material, the formula: 0.01≦a≦0.2 or 0.05≦a≦0.2 may be satisfied. In order to further increase the ionic conductivity of the solid electrolyte material, the formula: 0.01≦a≦0.15 or 0.05≦a≦0.15 may be satisfied. In order to further increase the ionic conductivity of the solid electrolyte material, the formula: 0.01≦a≦0.1 or 0.05≦a≦0.1 may be satisfied.
[0018] In order to increase the ionic conductivity of the solid electrolyte material, the formula: 0.8≦d≦1.2 may be satisfied in the composition formula (1). In order to further increase the ionic conductivity of the solid electrolyte material, the formula: 1.1≦d≦1.2 may be satisfied.
[0019] The solid electrolyte material according to the first embodiment may be crystalline or amorphous.
[0020] The shape of the solid electrolyte material according to the first embodiment is not limited. Examples of the shape are needle-like, spherical, or elliptical. The solid electrolyte material according to the first embodiment may be particles. The solid electrolyte material according to the first embodiment may be formed to have a pellet or plate shape.
[0021] For example, when the solid electrolyte material according to the first embodiment has a particulate shape (e.g., spherical shape), the solid electrolyte material according to the first embodiment may have a median diameter of 0.1 μm or more and 100 μm or less. The median diameter means a particle size at which the cumulative volume in the volumetric particle size distribution is 50%. The volumetric particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.
[0022] The solid electrolyte material according to the first embodiment may have a median diameter of 0.5 μm or more and 10 μm or less. This allows the first solid electrolyte material to have higher ion conductivity. Furthermore, the solid electrolyte material according to the first embodiment and other materials such as active materials can be dispersed well.
[0023] The solid electrolyte material according to the first embodiment may have a smaller median diameter than the active material, which allows the solid electrolyte material according to the first embodiment and the active material to be dispersed well.
[0024] <Method of manufacturing solid electrolyte material> The solid electrolyte material according to the first embodiment is produced, for example, by the following method.
[0025] Two or more kinds of halide raw material powders are mixed together to obtain a desired composition.
[0026] As an example, the desired composition is Li 2.9 Ca 0.05 Y 0.6 Gd 0.4 In the case of Br2Cl4, LiCl raw material powder, LiBr raw material powder, YCl3 raw material powder, GdCl3 raw material powder, and CaBr2 raw material powder (i.e., raw material powders of five kinds of halides) are mixed in a LiCl:LiBr:YCl3:GdCl3:CaBr2 molar ratio of approximately 1:1.9:0.6:0.4:0.05. The raw material powders may be mixed in a pre-adjusted molar ratio to offset composition changes that may occur in the synthesis process.
[0027] The raw material powders are reacted with each other mechanochemically (i.e., using the method of mechanochemical milling) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant may be calcined in a vacuum or inert atmosphere. Alternatively, a mixture of the raw material powders may be calcined in a vacuum or inert atmosphere to obtain a reactant.
[0028] By these methods, the solid electrolyte material according to the first embodiment can be obtained.
[0029] Second embodiment The second embodiment will be described below. The matters described in the first embodiment may be omitted as appropriate.
[0030] In the second embodiment, an electrochemical device will be described in which the solid electrolyte material according to the first embodiment is used. As an example of the electrochemical device according to the second embodiment, a battery will be described below.
[0031] The battery according to the second embodiment includes a positive electrode, an electrolyte layer, and a negative electrode. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material according to the first embodiment. The battery according to the second embodiment has excellent charge / discharge characteristics because it contains the solid electrolyte material according to the first embodiment.
[0032] The battery according to the second embodiment may be an all-solid-state battery.
[0033] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.
[0034] The battery 1000 includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203.
[0035] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .
[0036] The electrolyte layer 202 contains an electrolyte material (eg, a solid electrolyte material).
[0037] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .
[0038] The solid electrolyte particle 100 is a particle made of the solid electrolyte material according to the first embodiment, or a particle containing the solid electrolyte material according to the first embodiment as a main component.
[0039] The positive electrode 201 contains a material capable of absorbing and releasing metal ions such as lithium ions. The material is, for example, a positive electrode active material (for example, positive electrode active material particles 204).
[0040] Examples of the positive electrode active material include a lithium-containing transition metal oxide, a transition metal fluoride, a polyanion material, a fluorinated polyanion material, a transition metal sulfide, a transition metal oxyfluoride, a transition metal oxysulfide, or a transition metal oxynitride. Examples of the lithium-containing transition metal oxide include Li(NiCoMn)O2, Li(NiCoAl)O2, or LiCoO2.
[0041] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 can be well dispersed in the positive electrode 201. This improves the charge / discharge characteristics of the battery. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 improves. This allows the battery to operate at high power.
[0042] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This allows the positive electrode active material particles 204 and the solid electrolyte particles 100 to be dispersed well.
[0043] From the viewpoint of the energy density and output of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0044] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.
[0045] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, the solid electrolyte material according to the first embodiment. The electrolyte layer 202 may be a solid electrolyte layer.
[0046] The electrolyte layer 202 may be made of only the solid electrolyte material according to the first embodiment. Alternatively, the electrolyte layer 202 may be made of only a solid electrolyte material different from the solid electrolyte material according to the first embodiment.
[0047] Examples of solid electrolyte materials different from the solid electrolyte material according to the first embodiment are Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, where X' is at least one element selected from the group consisting of F, Cl, Br, and I.
[0048] Hereinafter, the solid electrolyte material according to the first embodiment will be referred to as a first solid electrolyte material, and a solid electrolyte material different from the solid electrolyte material according to the first embodiment will be referred to as a second solid electrolyte material.
[0049] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. In the electrolyte layer 202, the first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed. A layer made of the first solid electrolyte material and a layer made of the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.
[0050] The electrolyte layer 202 may have a thickness of 1 μm or more and 1000 μm or less. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 1000 μm or less, the battery can operate at high output.
[0051] The negative electrode 203 contains a material capable of absorbing and releasing metal ions such as lithium ions. The material is, for example, a negative electrode active material (for example, negative electrode active material particles 205).
[0052] Examples of the negative electrode active material are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicides. The metal material may be a single metal or an alloy. Examples of the metal material are lithium metal or lithium alloys. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), silicides, or tin compounds.
[0053] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 can be well dispersed in the negative electrode 203. This improves the charge / discharge characteristics of the battery. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 improves. This allows the battery to operate at high power.
[0054] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the solid electrolyte particles 100 to be dispersed well.
[0055] From the viewpoint of the energy density and output of the battery, in the negative electrode 203, the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0056] From the viewpoint of energy density and output, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.
[0057] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material for the purpose of increasing ion conductivity, chemical stability, and electrochemical stability.
[0058] As mentioned above, the second solid electrolyte material may be a halide solid electrolyte.
[0059] Examples of halide solid electrolytes are Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, where X' is at least one element selected from the group consisting of F, Cl, Br, and I.
[0060] Other examples of halide solid electrolytes are Li p Me q Y r Z6. Here, p+m'q+3r=6 and r>0 are satisfied. Me is at least one element selected from the group consisting of metal elements and metalloid elements other than Li and Y. The value of m' represents the valence of Me. The "metalloid elements" are B, Si, Ge, As, Sb, and Te. The "metal elements" are all elements included in Groups 1 to 12 of the periodic table (excluding hydrogen), and all elements included in Groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se). From the viewpoint of the ionic conductivity of the halide solid electrolyte, Me may be at least one element selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb.
[0061] The second solid electrolyte material may be a sulfide solid electrolyte.
[0062] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 It is.
[0063] The second solid electrolyte material may be an oxide solid electrolyte.
[0064] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or elemental substitutions thereof; (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4 or elemental substitutes thereof; (iv) Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an elemental substitution product thereof; or (v) Li3PO4 or its N-substituted derivatives It is.
[0065] The second solid electrolyte material may be an organic polymer solid electrolyte.
[0066] Examples of organic polymer solid electrolytes include a polymer compound and a lithium salt compound. The polymer compound may have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and therefore can further increase the ionic conductivity.
[0067] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0068] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.
[0069] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0070] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One type of non-aqueous solvent selected from these may be used alone, or a mixture of two or more types of non-aqueous solvents selected from these may be used.
[0071] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One type of lithium salt selected from these may be used alone. Alternatively, a mixture of two or more types of lithium salts selected from these may be used. The concentration of the lithium salt is, for example, 0.5 mol / liter or more and 2 mol / liter or less.
[0072] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0073] Examples of cations contained in ionic liquids are: (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium salts; (ii) aliphatic cyclic ammonium such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums.
[0074] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF 6- - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - It is.
[0075] The ionic liquid may contain a lithium salt.
[0076] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.
[0077] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, or carboxymethylcellulose. Copolymers may also be used as binders. Examples of such binders are copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. A mixture of two or more materials selected from the above materials may be used as a binder.
[0078] At least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive assistant for the purpose of increasing electronic conductivity.
[0079] Examples of the conductive additive include: (i) Graphites, such as natural or synthetic graphite; (ii) Carbon blacks, such as acetylene black or ketjen black; (iii) Conductive fibers, such as carbon or metal fibers; (iv) fluorocarbons; (v) Metal powders such as aluminium; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium dioxide; or (viii) Conductive polymers such as polyaniline, polypyrrole, or polythiophene In order to reduce costs, the above-mentioned conductive assistant (i) or (ii) may be used.
[0080] Examples of the shape of the battery according to the second embodiment are a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type. EXAMPLES
[0081] Hereinafter, the present disclosure will be described in more detail with reference to examples.
[0082] Example 1 (Preparation of solid electrolyte materials) In an argon atmosphere having a dew point of -60°C or less (hereinafter referred to as "dry argon atmosphere"), raw material powders of LiCl, LiBr, YCl3, GdCl3, and CaBr2 were prepared in a molar ratio of LiCl:LiBr:YCl3:GdCl3:CaBr2 of 1:1.9:0.6:0.4:0.05. These raw material powders were ground and mixed in a mortar. In this manner, a mixed powder was obtained. The mixed powder was milled at 600 rpm for 12 hours using a planetary ball mill. In this manner, a powder of the solid electrolyte material according to Example 1 was obtained. The solid electrolyte material according to Example 1 is composed of Li 2.9 Ca 0.05 Y 0.6 Gd 0.4 The composition was determined to be Br2Cl4.
[0083] The Li content per unit weight of the solid electrolyte material according to Example 1 was measured by atomic absorption spectrometry. The Ca content, Y content, and Gd content of the solid electrolyte material according to Example 1 were measured by high-frequency inductively coupled plasma atomic emission spectrometry. Based on the Li, Ca, Y, and Gd contents obtained from these measurement results, the Li:Ca:Y:Gd molar ratio was calculated. As a result, the solid electrolyte material according to Example 1 had a Li:Ca:Y:Gd molar ratio of 2.9:0.05:0.6:0.4, which was the same as the molar ratio of the raw material powder.
[0084] (Evaluation of ionic conductivity) FIG. 2 is a schematic diagram showing a pressure forming die 300 used for evaluating the ionic conductivity of a solid electrolyte material.
[0085] The pressure molding die 300 had an upper punch 301, a frame 302, and a lower punch 303. The upper punch 301 and the lower punch 303 were both made of electronically conductive stainless steel. The frame 302 was made of insulating polycarbonate.
[0086] Using the pressure molding die 300 shown in FIG. 2, the ionic conductivity of the solid electrolyte material according to Example 1 was measured by the following method.
[0087] In a dry atmosphere having a dew point of -30°C or less, the powder of the solid electrolyte material according to Example 1 (i.e., the powder of the solid electrolyte material 101 in FIG. 2) was filled into the inside of the pressure molding die 300. In the inside of the pressure molding die 300, a pressure of 300 MPa was applied to the solid electrolyte material according to Example 1 using an upper punch 301 and a lower punch 303.
[0088] While the pressure was still applied, the upper punch 301 and the lower punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper punch 301 was connected to a working electrode and a terminal for measuring potential. The lower punch 303 was connected to a counter electrode and a reference electrode. The impedance of the solid electrolyte material was measured by electrochemical impedance measurement at room temperature.
[0089] FIG. 3 is a graph showing a Cole-Cole diagram of the impedance measurement results.
[0090] In FIG. 3, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest was considered to be the resistance value for the ion conduction of the solid electrolyte material. The real value is indicated by the arrow R SEUsing the resistance value, the ionic conductivity was calculated based on the following formula (2). σ = (R SE ×S / t) -1 (2) Here, σ represents ionic conductivity. S represents the contact area of the solid electrolyte material with the punch upper portion 301 (equal to the cross-sectional area of the hollow portion of the frame mold 302 in FIG. 2). R SE represents the resistance value of the solid electrolyte material in impedance measurement, and t represents the thickness of the solid electrolyte material (i.e., the thickness of the layer formed from the powder 101 of the solid electrolyte material in FIG. 2).
[0091] The ionic conductivity of the solid electrolyte material according to Example 1 measured at 22° C. was 1.10×10 -3 S / cm.
[0092] (Battery Construction) In a dry argon atmosphere, the solid electrolyte material according to Example 1 and LiCoO2 were prepared in a volume ratio of 30:70. These materials were mixed in a mortar. In this way, a mixture was obtained.
[0093] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material according to Example 1 (100 mg), the above mixture (10 mg), and aluminum powder (14.7 mg) were laminated in this order. A pressure of 300 MPa was applied to this laminate to form a solid electrolyte layer and a first electrode. The solid electrolyte layer had a thickness of 500 μm.
[0094] Next, metal In (thickness: 200 μm) was laminated on the solid electrolyte layer, and a pressure of 80 MPa was applied to this laminate to form a second electrode.
[0095] Next, current collectors made of stainless steel were attached to the first and second electrodes, and current collecting leads were attached to the current collectors.
[0096] Finally, the inside of the insulating cylinder was isolated from the outside atmosphere by using an insulating ferrule, and the inside of the cylinder was sealed. In this manner, the battery according to Example 1 was obtained.
[0097] (Charge / discharge test) 4 is a graph showing the initial discharge characteristics of the battery according to Example 1. The initial charge / discharge characteristics were measured by the following method.
[0098] The battery according to Example 1 was placed in a thermostatic chamber at 25°C.
[0099] 72μA / cm 2 The battery according to Example 1 was charged until a voltage of 3.7 V was reached at a current density of 0.05 C, which corresponds to a 0.05 C rate.
[0100] Next, 72 μA / cm 2 The battery according to Example 1 was discharged at a current density of 0.1 V until a voltage of 1.9 V was reached.
[0101] As a result of the charge / discharge test, the battery according to Example 1 had an initial discharge capacity of 0.89 mAh.
[0102] <Examples 2 to 21> (Preparation of solid electrolyte materials) In Examples 2 to 19, LiCl, LiBr, YCl3, GdCl3, and CaBr2 were prepared as raw material powders in a molar ratio of LiCl:LiBr:YCl3:GdCl3:CaBr2 of (c-3d):(6-2a-c):(1-b)d:bd:a.
[0103] In Examples 20 and 21, LiCl, LiBr, YCl3, GdCl3, and CaBr2 were prepared as raw material powders in a molar ratio of LiCl:LiBr:YBr3:GdBr3:CaBr2 of c:(6-2a-c-3d):(1-b)d:bd:a.
[0104] Except for the above, the solid electrolyte materials according to Examples 2 to 21 were obtained in the same manner as in Example 1. The values of a, b, c, and d are shown in Table 1.
[0105] (Evaluation of ionic conductivity) The ionic conductivity of the solid electrolyte materials according to Examples 2 to 21 was measured in the same manner as in Example 1. The measurement results are shown in Table 1.
[0106] (Charge / discharge test) The solid electrolyte materials according to Examples 2 to 21 were used to obtain batteries according to Examples 2 to 21 in the same manner as in Example 1. The batteries according to Examples 2 to 21 were charged and discharged satisfactorily, like the battery according to Example 1.
[0107] <Comparative Examples 1 to 8> (Preparation of solid electrolyte materials) In Comparative Example 1, LiCl and YCl3 were prepared as raw material powders so that the molar ratio of LiCl:YCl3 was 3:1.
[0108] In Comparative Example 2, LiCl, LiBr, and YCl3 were prepared as raw material powders in a LiCl:LiBr:YCl3 molar ratio of 1:2:1.
[0109] In Comparative Example 3, LiCl, LiBr, and GdCl3 were prepared as raw material powders so that the molar ratio of LiCl:LiBr:GdCl3 was 1:2:1.
[0110] In Comparative Examples 4 and 5, LiCl, LiBr, YCl3, and CaBr2 were prepared as raw material powders so as to have a LiCl:LiBr:YCl3:CaBr2 molar ratio of (c-3d):(6-2a-c):(1-b)d:a.
[0111] In Comparative Examples 6 to 8, LiCl, LiBr, YCl3, and GdCl3 were prepared as raw material powders so as to have a LiCl:LiBr:YCl3:GdCl3 molar ratio of (c-3d):(6-2a-c):(1-b)d:bd.
[0112] Except for the above, the solid electrolyte materials according to Comparative Examples 1 to 8 were obtained in the same manner as in Example 1. The values of a, b, c, and d are shown in Table 2.
[0113] (Evaluation of ionic conductivity) The ionic conductivity of the solid electrolyte materials according to Comparative Examples 1 to 8 was measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0114] [Table 1]
[0115] [Table 2]
[0116] ≪Consideration≫ As is clear from Table 1, the solid electrolyte materials according to Examples 1 to 21 had a melting point of 8×10 -4 It has high ionic conductivity of over S / cm.
[0117] As is clear from a comparison of Examples 2 and 4 to 7 with Comparative Example 7, when the value of a, which represents the molar fraction of Ca, is 0.05 or more and 0.3 or less, the solid electrolyte material has high ionic conductivity. As is clear from a comparison of Examples 2 and 4 to 6 with Example 7, when the value of a is 0.05 or more and 0.2 or less, the ionic conductivity is further increased. As is clear from a comparison of Examples 2, 4, and 5 with Example 6, when the value of a is 0.05 or more and 0.15 or less, the ionic conductivity is further increased. As is clear from a comparison of Examples 2 and 4 with Example 5, when the value of a is 0.05 or more and 0.1 or less, the ionic conductivity is further increased.
[0118] Even if the value of a is less than 0.05, it is considered that the solid electrolyte material has high ionic conductivity. The value of a may be, for example, 0.01 or more and 0.3 or less.
[0119] As is clear from Examples 11 and 14 to 17, when the value of d, which represents the amount of Li deficiency or excess from the stoichiometric ratio, is 0.8 or more and 1.2 or less, the solid electrolyte material has high ionic conductivity. As is clear from comparing Examples 16 and 17 with Examples 11, 14, and 15, when the value of d is 1.1 or more and 1.2 or less, the ionic conductivity is further increased.
[0120] In all Examples 1-21, the batteries were charged and discharged at room temperature.
[0121] The solid electrolyte materials according to Examples 1 to 21 do not contain sulfur and therefore do not generate hydrogen sulfide.
[0122] As described above, the solid electrolyte material according to the present disclosure is suitable for providing a battery that has high lithium ion conductivity and can be charged and discharged well. [Industrial Applicability]
[0123] The solid electrolyte material of the present disclosure is used, for example, in batteries (for example, all-solid-state lithium ion secondary batteries). [Explanation of symbols]
[0124] 100 solid electrolyte particles 101 Solid electrolyte material powder 201 Positive electrode 202 Electrolyte layer 203 Negative electrode 204 Positive electrode active material particles 205 Negative electrode active material particles 300 Pressure forming die 301 Punch top 302 Frame type 303 Punch bottom 1000 batteries
Claims
1. Li, Ca, Y, Gd, and X; X is at least one element selected from the group consisting of Cl and Br; Represented by the following composition formula (1): Li 6-2a-3d Ca a (Y 1-b Gd b ) d Br 6-c Cl c ... (1) Here, the following formula 0<a<3, 0<b<1, 0<c<6, and 0<d<1.5, is satisfied, Solid electrolyte material.
2. The formula: 0.01≦a≦0.3 is satisfied; The solid electrolyte material according to claim 1 .
3. The formula: 0.05≦a≦0.3 is satisfied; The solid electrolyte material according to claim 2 .
4. The formula: 0.01≦a≦0.2 is satisfied; The solid electrolyte material according to claim 2 .
5. The formula: 0.8≦d≦1.2 is satisfied; The solid electrolyte material according to claim 1 .
6. The formula: 1.1≦d≦1.2 is satisfied; The solid electrolyte material according to claim 5 .
7. positive electrode, a negative electrode, and an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 6. battery.
Citation Information
Patent Citations
Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery
JP2011129312A
Solid electrolyte for a negative electrode of a secondary battery and methods for the manufacture of an electrochemical cell
US20180205112A1
Solid electrolyte material, and cell
WO2018025582A1
Solid electrolyte composition and production method for solid electrolyte member
WO2020137189A1